Performance Evaluation of Tilt-based Vehicle Accident Report System Using Triple Modular Redundancy - Primananda, Rakhmadhany; Bagus Prabowo, Bayu; Budi, Agung Setia; Tri Ananta, Mahardeka; Abidin, Zainul (Faculty of Computer Science (FILKOM) Brawijaya University, 2023)
A vehicle accident report system was designed to detect accidents accurately and send message to related person. However, after accident, some components or modules can be damaged and it may cause failure of accident detection. Therefore, Triple Modular Redundancy (TMR) method was implemented in the system to mask faults within the modules and ensure the system to continue working. TMR is one of passive hardware redundancy methods. The system includes three MPU-6050 sensors functioning as vehicle tilt sensors to provide hardware redundancy, a TC9548A module serving as an I2C multiplexer, an Arduino Nano acting as a microcontroller and voter, and a NodeMCU ESP8266 responsible for transmitting message. Based on experiment results, the TMR system has a reliability value of 0.9928, a failure rate value of 0.0004/cycle, and accuracy of 3 sensor value of 85%. While, the non-redundancy system has a reliability value of 0.9286, a failure rate value of 0.0053/cycle, and accuracy of single sensor value of 57%. The results of the system process were sent to and displayed via an e-mail. It can be concluded that the TMR system has better performance than the non-redundancy one.